Nexilin Regulates Oligodendrocyte Progenitor Cell Migration and Remyelination and Is Negatively Regulated by Protease-Activated Receptor 1/Ras-Proximate-1 Signaling Following Subarachnoid Hemorrhage - Li, Qiang; Zhao, Hengli; Pan, Pengyu; Ru, Xufang; Zuo, Shilun; Qu, Jie; Liao, Bin; Chen, Yujie; Ruan, Huaizhen; Feng, Hua (Frontiers in Neurology, 2018)
Progressive white matter impairments caused by subarachnoid hemorrhage (SAH) contribute to cognitive deficits and poor clinical prognoses; however, their pathogenetic mechanisms are poorly understood. We investigated the role of nexilin and oligodendrocyte progenitor cell (OPC)-mediated repair in a mouse model of experimental SAH generated via left endovascular perforation. Nexilin expression was enhanced by the elevated migration of OPCs after SAH. Knocking down nexilin by siRNA reduced OPC migration both in vitro and in vivo and abridged white matter repair. By contrast, the protease-activated receptor 1 (PAR1), Ras-proximate-1 (RAP1) and phosphorylated Ras-proximate-1 (pRAP1) levels in white matter were elevated after SAH. The genetic inhibition of PAR1 reduced RAP1 and pRAP1 expression, further enhancing nexilin expression. When delivered at an early stage at a concentration of 25 μg/kg, thrombin receptor antagonist peptide along with PAR1 knockdown rescued the down-regulation of myelin basic protein (MBP) and improved remyelination at the later stage of SAH. Our results suggest that nexilin is required for oligodendrocyte progenitor cell migration and remyelination following SAH, as it negatively regulates PAR1/RAP1 signaling, thus providing a promising therapeutic target in white matter repair and functional recovery.